MAGIC - Seismic network MAGma in ICeland - Dahm, Torsten; Jousset, Philippe; Heimann, Sebastian; Milkereit, Claus; Hersir, Gylfi Páll; Magnússon, Rögnvaldur (GFZ Data Services, 2020)
Abstract In January 2020, a swarm of earthquakes started under Thorbjorn volcano, Reykjanes, SW Iceland, associated to the uplift of up to 0.5 cm per day. Concern in Iceland is growing and the Iceland Meteorological Office suggested that possibly magma was intruded in the crust at shallow depth (3 to 9 km). The GFZ is starting a seismological Hazard and Risk Team (HART) in cooperation with IMO, ISOR and the University of Iceland Waveform data are available from the GEOFON data centre, under network code 9H.